Experience and meaning in music performance - Clayton, Martin; Dueck, Byron; Leante, Laura (Oxford University Press, 2013)
This text explores how the immediate experience of musical sound relates to processes of meaning construction and discursive mediation. A unique multi-authored work that both draws on and contributes to current debates in ethnomusicology, musicology, psychology, and cognitive science, it presents a novel and productive view of how cultural practice relates to the experience and meaning of musical performance.